Crisis management during anaesthesia: myocardial ischaemia and infarction. Issue 3 (2nd June 2005) - Ludbrook, G L; Webb, R K; Currie, M; Watterson, L M
Abstract : Background: Myocardial ischaemia and infarction are significant perioperative complications which are associated with poor patient outcome. Anaesthetic practice should therefore focus, particularly in the at risk patient, on their prevention, their accurate detection, on the identification of precipitating factors, and on rapid effective management. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK" supplemented by a specific sub-algorithm for myocardial ischaemia and infarction in the management of myocardial ischaemia and/or infarction occurring in association with anaesthesia. Methods: The potential performance of this structured approach for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual management as reported by the anaesthetists involved. Results: Of the 125 incidents retrieved from the 4000 reports, 40 (1%) were considered to demonstrate myocardial infarction or ischaemia. The use of the structured approach described in this paper would have led to appropriate management in 90% of cases, with the remaining 10% requiring other sub-algorithms. It was considered that the application of this structured approach would have led to earlier recognition and/or better management of the problem in 45% of cases. Conclusion: Close and continuous monitoring of patients at risk of myocardial ischaemia during anaesthesia is necessary, using optimal ECG lead configurations, but sensitivity of this monitoring is not 100%. Coronary vasodilatation with glyceryl trinitrate (GTN) should not be withheld when indicated and the early use of beta blocking drugs should be considered even with normal blood pressures and heart rates.